Evaluating the Current Status of Latakia’s International Container Terminal (LICT) using ARENA Software - محمد علاء الدين; سماح عبد الوهاب (Latakia University Journal -Engineering Sciences Series, 2023)
Simulation is an essential way to represent the various operations within the sea container terminal to predict their behavior and evaluate their performance due to the important role of container transport within the logistics chains of shipping around the world. We provided a separate simulation model for the operations of the Lattakia International Container Terminal LICT in its current state using the ARENA 14.0 program. These operations include berths, gantry and mobile cranes, arriving and departing ships and the various changes in them and their impact on the outputs of the model, which include the times of ships staying in the port and waiting times. As a result, the mentioned times are relatively large and the terminal will not be able to meet the increasing demand for containers in the future.